Quality and safety in prehospital airway management – retrospective analysis of 18,000 cases from an air rescue database in Germany - Ulf Lorenzen; Hartwig Marung; Christine Eimer; Andrea Köser; Stephan Seewald; Marcus Rudolph; Florian Reifferscheid (BMC Emergency Medicine, 2024)
Abstract Background Prehospital airway management remains crucial with regard to the quality and safety of emergency medical service (EMS) systems worldwide. In 2007, the benchmark study by Timmermann et al. hit the German EMS community hard by revealing a significant rate of undetected oesophageal intubations leading to an often-fatal outcome. Since then, much attention has been given to guideline development and training. This study evaluated the incidence and special circumstances of tube misplacement as an adverse peri-intubation event from a Helicopter Emergency Medical Services perspective. Methods This was a retrospective analysis of a German helicopter-based EMS database from January 1, 2012, to December 31, 2020. All registered patients were included in the primary analysis. The results were analysed using SPSS 27.0.1.0. Results Out of 227,459 emergency medical responses overall, a total of 18,087 (8.0%) involved invasive airway management. In 8141 (45.0%) of these patients, airway management devices were used by ground-based EMS staff, with an intubation rate of 96.6% (n = 7861), and alternative airways were used in 3.2% (n = 285). Overall, the rate of endotracheal intubation success was 94.7%, while adverse events in the form of tube misplacement were present in 5.3%, with a 1.2% rate of undetected oesophageal intubation. Overall tube misplacement and undetected oesophageal intubation occurred more often after intubation was carried out by paramedics (10.4% and 3.6%, respectively). In view of special circumstances, those errors occurred more often in the presence of trauma or cardiopulmonary resuscitation, with rates of 5.6% and 6.4%, respectively. Difficult airways with a Cormack 4 status were present in 2.1% (n = 213) of HEMS patients, accompanied by three or more intubation attempts in 5.2% (n = 11). Conclusions Prehospital airway management success has improved significantly in recent years. However, adverse peri-intubation events such as undetected oesophageal intubation remain a persistent threat to patient safety. Trial registration The study was registered in the German Register for Clinical Studies (number DRKS00028068).